Prospects for Fluorescence Molecular In Vivo Liquid Biopsy of Circulating Tumor Cells in Humans - Niedre, Mark (Frontiers in Photonics, 2022)
Our team recently developed “Diffuse in vivo Flow Cytometry” (DiFC) for detection and enumeration rare circulating tumor cells (CTCs) in mice with highly-scattered fluorescent light. We have used DiFC to study dissemination of CTCs in a number of mouse models of metastasis with fluorescent protein expressing cells. Because DiFC uses diffuse light and interrogates large blood vessels in relatively deep tissue, in principle it could be translated to larger limbs, species, and even humans clinically. In this perspective, we discuss the technical challenges of human translation of DiFC in the context of the current state of the technology, as well as potential strategies for labeling of CTCs with targeted fluorescent molecular probes. We also discuss potential advantages and disadvantages of DiFC as a clinical or research tool. In principle, DiFC could represent a powerful complementary technique (to liquid biopsy blood draws) for accurate and sensitive measurement of changes in CTC numbers over time.